Headspace vapor components in fresh and canned mango juices - Ong, Paz T.
Volatile components emanating from canned mango juices were analyzed by using a Varian Aerograph A-Model 600 B Hy-Fi Gas Chromatograph equipped with hydrogen flame detector. Fresh mango juices were allowed to stand for 5 hours before the accumulated headspace volatiles were withdrawn. Processed canned mango juices were stored for 12 weeks at room temperature until conditions (as indicated by physico-chemical analyses and gas chromatography) become stabilized. Fresh and newly mango juices indicated the presence of only one distinct peak - Peak #3. However, prolonged storage showed the presence of another major peak of low volatility - Peak #4. Identification of the isolated volatile was based on the comparison of retention times of the unknown and the standard known compounds using the same identical conditions. The volatiles were tentatively identified as Ethanol with possible combination of Ethyl Acetate and Benzyl Alcohol. Traces of Acetaldehyde maybe present in the headspace. Physico-chemical analyses showed no significant changes beyond the 5th week of storage. Canned mango juices showed slight significant changes beyond the 5th week of storage. Further storage showed a stable pH value of 3.5 and 3.7 for Trial 1 and Trial 2 respectively. Soluble solids remained stabilized ranging from 30 to 36 in both trials. Percent titrable acidity stayed within a close range.